TINDAK PIDANA PELANGGARAN LALU LINTAS YANG DILAKUKAN PELAJAR SMP (Studi Penelitian di Polres Langkat - Teguh T; Sumiadi S; Joelman Subaidi (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2021)
Abstract The occurrence of traffic violations committed by junior high school students in the legal area of ​​Langkat Police. Real facts in the field, it is estimated that around 46 students from the 2 schools studied, namely the Hangtua Stabat Private Junior High School and the AL-Maksum Stabat Private Junior High School every day use motorbikes to school. this fact is clearly a violation of the law because junior high school children do not yet have a SIM, because to be able to have a SIM there is Law no. 22 of 2009 Article 77 Paragraph (1) at least 16 years old while junior high school students are only 13 to 15 years old. Due to their relatively young age, junior high school children are psychologically immature and do not understand well the dangers that can be caused by motorbikes. So that in addition to violations that occur by driving using a motorcycle, not having a SIM, not wearing a helmet and modifying a motorcycle. the problem is, what are the factors that cause students to violate traffic laws in the use of motorbikes? What are the efforts of the Langkat Police in tackling traffic violations committed by students in the use of motorbikes? The research method in this thesis uses an empirical juridical research method with a statutory and case approach. the nature of the research used is descriptive. Sources of data used, namely primary data and secondary data. The results of this study indicate that various efforts have been made by the local police in tackling traffic violations committed by students, one of which is in the form of outreach to schools, warnings and fines for students who commit traffic violations. This is expected to be able to provide a deterrent effect for students to pay more attention to the completeness of motorized vehicle administration and also the rules for driving so as to create an orderly traffic. The author suggests schools in Langkat district to harmonize the existing regulations in schools with the Langkat police regulations. Keywords: Violation, Student, Traffic